Suicidality is most centrally situated within network of depression symptom criteria in unipolar depression patients with mood stabilizer in Asia - Yoon, Jin Woong; Kim, Eunkyung; Jeong, Narae; Kang, Minseok; Kim, Han Seul; Lee, Seonjae; Yoon, Hyung Jun; Kim, Seung Gon; Na, Euihyeon; Yang, Hyunju; Park, Joon Hyuk; Yang, Shu Yu; et al. (Asian Journal of Psychiatry, 2024)
Lithium and mood stabilizers are considered effective augmentation agents of antidepressants for treatment-resistant depression. Thus, this study aimed to estimate the network structure of depression symptom criteria among unipolar depression patients with mood stabilizers, using data from the Research on Asian Psychotropic Prescription Patterns for mood stabilizers (REAP-MS). We estimated a network of the 9 depression symptom criteria among 411 unipolar depression patients in Asia. Each of the depression symptom criteria was considered to be a dichotomous categorical variable. Suicidality (suicidal ideation or attempt) was the most centrally situated within the network of depression symptoms, followed by depressed mood, loss of energy, anhedonia and weight loss or gain. Contrastingly, concentration problem was the least interconnected. The depression symptom criteria were organized into 4 clusters by the community detection method. The findings suggest that suicidality may be one of the significant therapeutic target symptoms in unipolar depression patients with mood stabilizers.
Keywords: Adult; Antidepressive Agents; Antimanic Agents; Asia; Depressive Disorder, Major; Depressive Disorder, Treatment-Resistant; Female; Humans; Male; Middle Aged; Suicidal Ideation; Suicide, Attempted; Young Adult; Asia; Lithium; Mood stabilizer; Network analysis; Suicidality; Unipolar depression